SCAN&GO Il nuovo modo di fare Topografia - S.R.L., SCAN&GO (GEOmedia, 2013)
L'articolo propone una nuova metodologia per il rilievo topografico del territorio che utilizza strumentazione laser scanner abbinata a ricevitori GPS. Il sistema, installato su autoveicolo in modalità "Rileva e Vai”, è studiato per ottenere una definizione tridimensionale centimetrica di singole scansioni in un unico sistema di riferimento. Scan&Go is a new method for the topographical survey of the area using laser scanner combined with GPS receivers. The system, installed on vehicle mode "Detect and Go" (Patent Pending) is designed to obtain a three-dimensional definition centimeter of individual scans into a single reference system. This methodology arises from the need to make faster and more productive use of the new systems terrestrial laser scanner in the field of traditional survey, stimulating the transition from the method of timely relief to that of the three-dimensional virtual reality allowing its use also in daily Topography classic.